A 2015 survey of established or potential epigenetic biomarkers for the accurate detection of human cancers. (3rd July 2016) - Amacher, David E.
Abstract: Context The silencing or activation of cancer-associated genes by epigenetic mechanisms can ultimately lead to the clonal expansion of cancer cells.Objective The aim of this review is to summarize all relevant epigenetic biomarkers that have been proposed to date for the diagnosis of some prevalent human cancers.Methods A Medline search for the terms epigenetic biomarkers, human cancers, DNA methylation, histone modifications and microRNAs was performed.Results One hundred fifty-seven relevant publications were found and reviewed.Conclusion To date, a significant number of potential epigenetic cancer biomarkers of human cancer have been investigated, and some have advanced to clinical implementation.